On Beta-Prime Submodules - Thawatchai Khumprapussorn (Journal of the Indonesian Mathematical Society, 2019)
We introduce the concepts of $β$-prime submodules and weakly $β$-prime submodules of unital left modules over a commutative ring with nonzero identity. Some properties of these concepts are investigated. We use the notion of the product of two submodules to characterize $β$-prime submodules of a multiplication module. Characterization of $β$-prime and weakly $β$-prime submodules of arbitary modules are also given.